HUBUNGAN ANTARA EMOTIONAL INTELLIGENCE DENGAN SEMANGAT BELAJAR PESERTA DIDIK KELAS VIII DI MTs SRIWIJAYA KECAMATAN BANDAR SRIBHAWONO KABUPATEN LAMPUNG TIMUR PROVINSI LAMPUNG - Husna Lutfiah (PAI RAFAH, 2021)
This study focuses on several triggers that give encouragement or encouragement to improve learning outcomes based on students' emotional intelligence and motivation in class VIII students at MTs Sriwijaya, Desa Sadar Sriwijaya, Kec. Bandar Sribhawono, Lampung Province.In this study, researchers used a quantitative formula from the results of the questionnaire whose results were processed in a correlation formula with multiple correlations, namely emotional intelligence and learning motivation which were independent variables with the learning outcomes of MTs Sriwijaya students which were the dependent variable, this research was included in the type of correlation research. by using the following formula: Ry.12 = √